Teacher’s Performance Based on to Professional Standards of Teachers Under the Office of Samut Prakan Provincial Primary Education Area 1 - Yoosung, Sukanda; Sittitool, Thairath (Ratchaphruek Journal, 2020)
The purpose of this research was to study the level of work performance based on professional standards of teachers under the Office of Samut Prakan Primary Educational Service Area 1, according to the regulations stated in Teachers’ Council Act, B.E. 2556-professional standards. The population of this study were 1,918 teachers under the Samut Prakan Primary Educational Service Area Office 1. The sample subject consisted of 320 teachers randomly selected through the use of tables. The tools used for data collection were questionnaires with 5 rating scales. Data were analyze by frequency, percentage, mean, and standard deviation. The research showed that the overall level of work performance based on professional standards of teachers under the Office of Samut Prakan Primary Educational Service Area 1, was found at a very good level ( = 4.67). When each work performance under each standard was considered and put in descending order, the following three performances were found at a very good level. The work performance with lowest mean, but at a good level was standard 5-continuously improve teaching media for their effectiveness ( = 4.50)